Lourdes Arizpe A Mexican Pioneer in Anthropology - Arizpe, Lourdes; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book presents major texts by Prof. Dr. Lourdes Arizpe Schlosser, a pioneering Mexican anthropologist, on the occasion of her 70th birthday. She is a leading researcher into indigenous peoples, an innovator in women$1 (Bs studies and a global scientific leader who has inspired the international research and policy communities. Throughout her distinguished career she has analysed ethnicism and indigenous peoples, women in migratory flows, cultural and social sustainability and intangible cultural heritage as social capital, placing these issues on the world agenda for research and policy. Several of the 12 major texts in this volume have been published since 1972 in the US, Europe, Latin America and India; some were first published in Spanish and are available in English for the first time. This anthology also includes recent unpublished texts on culture, development and international cultural policy delivered at high-level international meetings.s
A Brief Biography of the Author -- Selected Bibliography of Lourdes Arizpe Schlosser -- The Dialogue on the Diversity of Cultures and Civilizations -- On the Cultural and Social Sustainability of World Development -- The Global Cube -- The Culture of the Ax, the Machete, and the Sling -- Relay Migration and the Survival of the Peasant Household -- Agrarian Change and Women$1 (Bs Rural Out-migration in Latin America -- Women in the Informal Labour Sector: the Case of Mexico City -- Cultural Change and Ethnicity on Rural Mexico -- The Challenge of Cultural Pluralism: The First National Congress of Indigenous Peoples 1975 -- Perception and Ideology in Interethnic Relations -- Indian Cultures in Mexico City -- Zacatipan Kinship Terminology: A Dual Approach.s
Keywords: Environmental sciences; Science -- History; Environmental law; Anthropology; Environment; Environmental Law/Policy/Ecojustice.; History of Science; Anthropology